Synthesis and spectral characterisation of bis[3,4-dichlorophenylltin(lV) dichloride complexes. The X-ray crystal structure of the 4,4’-dimethyl2,2’-bipyridyl adduct of bis[3,4-dichlorophenylltin dichloride - Lo, Kong-Mun; Yap, Chee-Keong; Kumar Das, V. G. (Malaysian Journal of Science, 1995)
The synthesis and spectroscopic data ( 119Sn NMR, 119ntSn Mössbauer, IR) of a series of six-coordinated diorganotin(IV) complexes of the type R2SnC12.L2 and R2SnL’ where R = 3,4-dichlorophenyl, L = neutral monodentate oxygen donor ligand (containing >S=O, P=O or As=O grouping) or 1/2 bidentate donor [2,2’-bipyridine (bipy), 4,4’-dimethyl-2,2’-bipyrdine (M%bipy), 1,10-phenanthroline (phen), 3,4,7,8-tetramethyl -l, 10-phenanthroline (Me4phen)]; L’ = 8-quinolinolato (oxin) or 2-methyl-8-quinolinolato (Meoxin) are presented. The quadrupole splitting (QS) values of ca. 3.60 mm s-l for the adducts with monodentate ligands are in accord with essentially trans-[SnR ] octahedral structures. The complexes of (3,4- C12C6H3) SnC12 with bipy and phen yielded QS values of ca. 2 mm s-l which suggest cis-[SnR2] octahedral geometries. In contrast, the SnC12. Meohen adduct has a QS value of 3.17 mm s-l indicative of a distorted trans-[SnR2] octahedral geometry or a skew-trapezoidal bipyramidal geometry. The Mössbauer spectrum for the indicates this to be a homogenous mixture of cis- and trans-[SnR2] isomers. X-ray analysis of the crystalline product obtained from a toluene solution of this compound this to be exclusively the trans isomer [C-Sn-C NI-Sn-N2 Cll-Sn-C12 sn-c 2.14(1), 2.15(1) Ã…, Sn-Cl 2.462(3), 2.467(3) and sn-N 2.313(9), 2.335(9) Ã…]. The bischelates, and have p values (p = QS/IS) > 2.1 which indicate higher-than-four coordination environments at tin for these complexes. The low QS values of ca. 1.50 mm s-l for the bischelates are rationalised in terms of cis-[SnR2] octahedral structures. The large 119Sn NMR chemical shifts measured for the adducts and the bischelates in CDC13 (-420 ppm to -350 ppm) indicate that the diorganotin complexes retain their octahedral tin configurations in solution.